Developing Universal Design for Learning Asynchronous Training in an Academic Library - Lewitzky, Rachael A.; Weaver, Kari D. (Partnership, 2021)
This paper explores the design and initial implementation of online training modules for Universal Design for Learning in the context of academic libraries. Academic libraries are shifting away from the provision of resources and toward actively providing instruction and engaging with learners. The COVID-19 pandemic saw a quick transition from many in-person resources to virtual resources. Ensuring librarians are equipped to support learners in this manner is crucial. The goal of this paper was to determine how best to assist academic librarians with developing effective online resources. To achieve this goal, we conducted interviews with academic librarians. After consulting the literature and collecting information from academic librarians, we identified four key concepts for providing valuable instruction and designing material. The four themes included making content accessible, usable, meaningful, and reliable. We then developed four online training modules using Articulate Rise. The modules provide a foundation for aiding academic librarians with their teaching practice and engaging with a broad range of learners. These modules quickly demonstrated their value in the library context, and future testing, assessing, and iterating will enable their continuous improvement via institutional and cross-institutional collaboration.